A New Perspective on Anhedonia in Schizophrenia - Strauss, Gregory P. (2012)
OBJECTIVE: Previous research provides evidence for discrepancies among various types of emotional self-report in individuals with schizophrenia, such that patients report similar levels of positive emotion to controls when reporting current feelings, yet diminished levels of positive emotion when reporting on non-current feelings. These apparent discrepancies have come to be termed “the emotion paradox” in schizophrenia, and made it increasingly difficult to understand what anhedonia actually reflects in this patient population. METHOD: In the current manuscript, we review the literature on emotional experience in schizophrenia through the lens of a well-validated model of emotional self-report developed in the affective science literature that clarifies the sources of emotion knowledge that individuals access when providing different types of self-report. We use this model to resolve the “emotion paradox” and provide a new psychological conceptualization of anhedonia. RESULTS: Data are presented in support of this new perspective on anhedonia, and to demonstrate how cognitive impairments may influence reports of non-current feelings in schizophrenia. CONCLUSIONS: We conclude that anhedonia should no longer be considered an experiential deficit or a diminished “capacity” for pleasure in schizophrenia. Rather, anhedonia reflects a set of beliefs related to low pleasure that surface when patients are asked to report their non-current feelings. Encoding and retrieval processes may serve to maintain these beliefs despite contrary real-world pleasurable experiences. Implications for assessment and treatment are discussed in relation to this new conceptualization of anhedonia.